Avaliação da qualidade metodológica de meta-análises sobre intervenções para a redução da reiteração infracional juvenil - Guimarães, Lyara Correia (2025)
The methodological quality used in research impacts its results and may produce biases. Therefore, a systematic review of other systematic reviews and meta-analyses on the effectiveness of psychosocial intervention programs to reduce reoffending among young offenders was carried out, aiming to describe their characteristics and evaluate their methodological rigor. Among the 25 articles included, it was found that the majority (n=15) came from the United States, and most of the studies (n=20) performed meta-analytic calculations rather than narrative syntheses. Furthermore, the articles included showed an increasing production from the year 2000 onwards, with publications between 1985 and 2023. The methodological quality of most articles (n=18) was classified as critically low by the AMSTAR-2 tool. The characteristics of the included articles can be understood through historical data on the sociopolitical development of the juvenile justice system and the scientific development of the meta-analytic method itself. In turn, the low methodological quality observed points to a lack of transparency in the production of meta-analysis reports in the field of study focused on the effectiveness of psychosocial interventions. Thus, some possible ways to bridge the existing gaps are discussed.